Exploring diverse food system actor perspectives on gene editing: a systematic review of socio-cultural factors influencing acceptability - Henderson K; Lang B; Kemper J; Conroy D (Springer Nature B V, 2024)
Despite the promise of new gene editing technologies (GETs) (e.g., CRISPR) in accelerating sustainable agri-food production, the social acceptability of these technologies remains unclear. Prior literature has primarily addressed the regulatory and economic issues impacting GETs ongoing acceptability, while little work has examined socio-cultural impacts despite evolving food policies and product commercialisation demanding input from various actors in the food system. Our systematic review across four databases addresses this gap by synthesising recent research on food system actors’ perspectives to identify the key socio-cultural factors influencing GET acceptability. This review extends prior literature by including views from a more diverse range of actors (e.g., farmers and NGOs) and provides a better understanding of their perceived social benefits and concerns. We find food system actors perceive positive and negative impacts of using GETs in agriculture. These perspectives are often entangled in broader debates regarding sustainability and food systems issues (e.g., social justice). We discuss practical recommendations for policymakers, agri-food industry managers, and scientists to better align gene edited foods (GEFs) with food system actors’ values. GEF policy, development, and commercialisation must reflect social values such as collective wellbeing and transparency to improve actors’ acceptability. More research is required among marginalised food actors such as Indigenous and smallholder farmers.
Keywords: Gene editing; CRISPR; Agri-food production; Food system actors; Acceptance; Socio-cultural factors